Community Participation of the “Kampung KB” Program: Study in Malang City Year 2020 - Rany Ekawati; Ema Novita Deniati; Anindya Hapsari; Lu'luim Mutakifah; Annisaa Annisaa; Lilik Ariyanti (Preventia : The Indonesian Journal of Public Health, 2024)
Indonesia has a significant population problem. The national population grows by a staggering 4.5 million people annually, and Malang is one example of a city experiencing this rapid growth. The government is implementing a program called "Kampung KB" to address this issue. The purpose of this research is to provide an overview of the participation of the people of “Kampung KB” Malang City. This study uses qualitative research with in-depth interviews, then analyzed using data triangulation. This research was conducted from September to December 2020. The research location was six “Kampung KB” in Malang City. The result of this research is that the implementation of “Kampung KB” in Malang City is carried out at the village level. In the “Kampung KB” there are fields, namely education, culture, social, economy, religion, environment, reproduction, protection, and love. Routine activities include service work, “Tri Bina”, long-term contraceptive methods, counseling, training and mentoring. Participation and enthusiasm of the community, which is quite good, is one of the benchmarks in developing these activities. But there is still less support from the government, especially regarding the budget for organizing “Kampung KB” activities, facilities and infrastructure such as places to hold activities in the “Kampung KB”.